Cultivar differences in carbon and nitrogen accumulation, balance, and grain yield in maize - Li, Qiang; Ren, Yun; Fu, Hao; Li, Zhexin; Kong, Fanlei; Yuan, Jichao (Frontiers in Plant Science, 2022)
The balance of carbon (C) and nitrogen (N) metabolism influences plant growth and development as well as yield. A two-year field experiment was conducted in a hilly region in southwest China in 2019–2020 to investigate the correlation between the accumulation and balance of C and N, as well as the grain yield of maize cultivars with contrasting N efficiencies. Using Zhenghong 311 (ZH 311) and Xianyu 508 (XY 508) as research sources, the differences in C and N accumulation and balance in maize cultivars with contrasting N efficiencies were compared to analyze the correlation between the accumulation and balance of C and N with grain yield. According to the results, the ZH 311 cultivar had higher C and N accumulation in each stage and grain yield than the XY 508 cultivar, while the C/N ratio in each stage and organ was significantly lower in ZH 311 than in XY 508, with the greatest difference occurring in the silking stage and leaf, indicating that the N-efficient cultivar ZH 311 had evident advantages in accumulation and balance of C and N and grain yield than the N-inefficient cultivar XY 508. Moreover, the C and N accumulation and grain yield increased significantly with N application, while the C/N ratio in each stage and organ decreased significantly with N application, but the differences between ZH 311 and XY 508 increased first and then decreased with the increase of N level, the optimum N level when obtaining the highest grain yield of ZH 311 (273.21 kg ha–1) was significantly lower than that of XY 508 (355.88 kg ha–1). Furthermore, grain yield was positively correlated with C (R2 = 0.9251) and N (R2 = 0.9033) accumulation, affected by pre-anthesis N (R2 = 0.9198) and post-anthesis C (R2 = 0.8632) accumulation, and negatively correlated with the C/N ratio (R2 = 0.7664), with the highest correlation between grain yield and the C/N ratio in silking stage (R2 = 0.7984) and leaf (R2 = 0.7616). In conclusion, the N-efficient cultivar ZH 311 could better coordinate the C and N balance of the plant, especially the C and N balance in the silking stage and leaf, promote photosynthetic product storage and transport, prolong the leaf function period, and make the pre-anthesis and post-anthesis C and N accumulation of ZH 311 significantly higher than those of XY 508, allowing higher grain yields.